2011
DOI: 10.5194/acp-11-147-2011
|View full text |Cite
|
Sign up to set email alerts
|

The vorticity budget of developing typhoon Nuri (2008)

Abstract: Abstract. The formation of west Pacific tropical cyclone Nuri (2008) was observed over four days from easterly wave to typhoon stage by aircraft using scanning Doppler radar and dropsonde data. This disturbance developed rapidly in a significantly sheared environment. In spite of the shear, overlapping closed circulations existed in the frame of reference of the storm in the planetary boundary layer and at 5 km elevation, providing a deep region protected from environmental influences. The rapid spinup of Nur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(49 citation statements)
references
References 31 publications
2
47
0
Order By: Relevance
“…The new model finds strong support in the four-season observational survey of the Atlantic and eastern Pacific sectors carried out by DMW09, two recent case studies in the western Pacific sector during the Tropical Cyclone Structure 2008 (TCS08) field experiment (Montgomery et al 2010a;Raymond and López-Carillo 2011), the post-analysis of the 2009 PREDICT Dry Run (Wang et al 2011), and realcase and idealized high-resolution numerical model simulations (Wang et al 2010a,b;Montgomery et al 2010b;Fang andZhang 2010, 2011). Together, these studies point to the pouch center as the preferred location (or "sweet spot") for cyclogenesis, serving as a "focal point" for an upscale vorticity aggregation process while the wave pouch and proto-vortex move together.…”
Section: −1mentioning
confidence: 99%
“…The new model finds strong support in the four-season observational survey of the Atlantic and eastern Pacific sectors carried out by DMW09, two recent case studies in the western Pacific sector during the Tropical Cyclone Structure 2008 (TCS08) field experiment (Montgomery et al 2010a;Raymond and López-Carillo 2011), the post-analysis of the 2009 PREDICT Dry Run (Wang et al 2011), and realcase and idealized high-resolution numerical model simulations (Wang et al 2010a,b;Montgomery et al 2010b;Fang andZhang 2010, 2011). Together, these studies point to the pouch center as the preferred location (or "sweet spot") for cyclogenesis, serving as a "focal point" for an upscale vorticity aggregation process while the wave pouch and proto-vortex move together.…”
Section: −1mentioning
confidence: 99%
“…The vorticity tendency equation in pressure coordinates has a particularly concise form in which the local tendency can be written as the horizontal divergence of a horizontal flux (Haynes and McIntyre 1987;Raymond and Lopez-Carillo 2011;Tory et al 2012;Raymond et al 2014). Specifically, the equation for the local tendency of absolute vorticity ζ a may be written as…”
Section: Vorticity and Okubo-weiss Diagnosticsmentioning
confidence: 99%
“…The importance of recirculating flow in quasi-closed circulations for the development of tropical cyclones in tropical waves has been the subject of a number of recent studies Montgomery et al, 2010;Raymond and López Carrillo, 2011). The quasi-circulation contains an enhanced vortical environment that provides the background vorticity from which the TC vortex is constructed, and it offers protection from the intrusion of dry air that might disrupt the developing circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Raymond and López Carrillo (2011) have shown that vertical alignment of the pouch is not critical, but suggests there should be some overlap. This result is consistent with our experience, using data interpolated to a 1 • × 1 • grid, that an overlap which encompasses at least 2 neighbouring grid points is generally required.…”
Section: Low Deformation Vorticity: a Necessary Condition For Tc Formmentioning
confidence: 99%